2007
DOI: 10.1080/14034940701362137
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Prestige and its significance for medical specialties and diseases

Abstract: Medical specialities and diseases differ with regard to prestige. Characteristics related to specialties and diseases determine their prestige. The authors suggest that differences in prestige bear consequences for actual priority setting in healthcare systems, and contend that this should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 26 publications
4
99
0
3
Order By: Relevance
“…A number of studies have found perceived prestige, or lack thereof, to be associated with specific career choices. 13,[24][25][26][27] Role models have been found to broadly influence medical career choice. [28][29][30] Given that only 2.3% of students had a close family member or friend practising emergency medicine, it is likely that role models had not yet exerted an influence on career decision-making for most of the study population.…”
Section: ; 11 (3) 201mentioning
confidence: 99%
“…A number of studies have found perceived prestige, or lack thereof, to be associated with specific career choices. 13,[24][25][26][27] Role models have been found to broadly influence medical career choice. [28][29][30] Given that only 2.3% of students had a close family member or friend practising emergency medicine, it is likely that role models had not yet exerted an influence on career decision-making for most of the study population.…”
Section: ; 11 (3) 201mentioning
confidence: 99%
“…Hence, surgery, internal medicine and anaesthesiology are at the very top whereas psychiatry and general practice are generally low in prestige. This hierarchy has proved consistent across Norway (Norredam & Album, 2007), the United States (Rosoff & Leone, 1991) and Australia (Creed et al, 2010).…”
Section: Integration Vs Horizontal Segregation In the Labour Marketmentioning
confidence: 91%
“…Such differences in strategies or capacity may cancel out the differences in observed actual waiting time; for example to give access to less severely ill patients compensated by longer maximum waiting times. Differences in capacity may be associated with variation in funding, 15 or the prestige of different medical disciplines, 16,17 but our study was not designed to explore if this was the case. The Norwegian prioritization guidance documents also allow discretion when it comes to each single patient.…”
Section: Discussionmentioning
confidence: 99%